The Relationship between Peer Social Support and Academic Burnout for Students at the Annuriyah Islamic Boarding School, Demak - Eva Rusdiana Puspitasari; Kholifah Umi Sholihah (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
Students at traditional Muslim school can be at risk of experiencing academic burnout due to the many routines carried out while undergoing various activities at the cottage. This situation makes students need social support and attention from peers who experience similar problems. The aim of this study was to determine the relationship between peer social support and academic burnout for students at traditional Muslim school. This study involved 170 students at the Annuriyah Islamic Boarding School in Demak. Sampling was carried out using a saturated sampling technique. The peer social support measurement tool used has adequate reliability (️α=0.887), as well as the academic burnout measurement tool (️α=0.908). The analysis used is simple linear regression analysis. The results of this study found that peer social support was found to have a significant negative relationship with academic burnout, which means that the higher the support provided, the lower the perceived academic burnout. The effective contribution of peer social support to burnout is 41.2%. Based on the research results obtained, providing psychoeducation on the importance of support between friends in Islamic boarding schools needs to be done to prevent or overcome the problem of academic burnout for students.